KAJIAN HERMENIUTIKA PADA KARYA MAHAYASA DENGAN ARTIFICIAL INTELLIGENCE - Wijaya, I Putu Sinar; Budayana, I Wayan Gede (Warna Komunikasi, 2026)
This study examines the meaning of Mahayasa's digital artworks produced with the aid of Artificial Intelligence technology through a hermeneutic approach. Mahayasa's works, which combine traditional Nusantara cultural values ​​with modern AI-based aesthetics, present complex and multi-layered interpretative dimensions. Through the hermeneutic framework of Gadamer and Ricoeur, this study highlights how the process of "horizon fusion" between the cultural context of the work and the experience of the viewer opens up a dynamic dialogue of meaning. In addition, works produced by AI algorithms are understood as the result of collaboration between machines and human creativity, forming a "digital hermeneutic circle" in which meaning continues to evolve. This study shows that although Artificial Intelligence technology facilitates the creation process, the interpretative aspects and aesthetic value still depend on the active role of the artist and the viewer. Thus, Mahayasa's AI-based works not only represent technological innovation in art but also maintain philosophical depth through an open and layered interpretative space.